(untitled) (Architecture Image Studies, 2026)
The COVID-19 pandemic has accelerated the adoption of flexible and sustainable work practices, raising important questions about their impact on employees’ work–life balance (WLB). This conceptual paper develops a theoretical model linking sustainable work practices namely flexible work arrangements, remote work, job sharing, and supportive leave policies to improved employee WLB and proposes organizational support as a key moderating influence. Drawing on Conservation of Resources Theory, these work practices function as valuable resources that help employees reduce work–family conflicts and stress. Social Exchange Theory provides a lens for understanding how strong organizational support can amplify these benefits as employees reciprocate supportive cultures with greater engagement and well-being. Work–family Border Theory is used to contextualize WLB emphasizing the management of boundaries between work and personal life. We present propositions for each proposed relationship and discuss how organizational support can strengthen the positive effects of sustainable work initiatives on WLB. The article concludes with implications for human resource management practice and future research directions, particularly in the post-pandemic context of Malaysia’s financial sector. By integrating multiple theoretical perspectives, this paper offers a robust framework for understanding how sustainable work practices can foster a healthier WLB in modern-day organizations.